Effects of Emicizumab on APTT, FVIII assays and FVIII Inhibitor assays using different reagents: Results of a UK NEQAS proficiency testing exercise. Issue 6 (23rd October 2020) - Lowe, Anna; Kitchen, Steve; Jennings, Ian; Kitchen, Dianne P.; Woods, Tim A. L.; Walker, Isobel D.
Abstract: Introduction: Emicizumab (Hemlibra: Roche Switzerland) is a, humanized, bi‐specific monoclonal modified immunoglobulin G4 (IgG4) which binds human FX, FIX and activated FIX (FIXa) to mimic activated FVIII activity. Aim: Evaluate the effects of emicizumab on the APTT, surrogate FVIII activity and FVIII inhibitor results. Methods: Two samples were provided, one obtained from an emicizumab treated severe haemophilia A patient with FVIII inhibitors and one constructed by in vitro addition of emicizumab using plasma from a severe haemophilia A patient without FVIII inhibitors. An APTT screen, surrogate FVIII and FVIII inhibitor tests were performed on both samples by participating centres. Results: APTT results were below the lower limit of normal range. Chromogenic FVIII assay results with the Hyphen/Biophen human component‐based assay gave higher than expected coefficient of variation (CV) results, 38%–40%. The modified one‐stage FVIII assay with emicizumab calibrators showed similar results regardless of the APTT reagent. Inhibitor assay median results for sample S18:23 = 1.43 BU (range 0.9‐3.0 BU/ml, CV 38%). S18:24 was classified as below the lower limit of detection. Conclusion: APTT screens showed a consistent shortening. Unmodified one‐stage Factor VIII assay results were remarkably high. APTT‐based assays are unsuitable for measurement of coagulation factors or inhibitors in patients treated with emicizumab. Bovine origin chromogenic assays are insensitive to emicizumab and should be used to monitor FVIII levels/FVIII inhibitors in emicizumab treated patients. Product‐specific calibrators should be implemented to reduce result variability.